2015
DOI: 10.1007/s10753-015-0265-3
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and Anti-oxidative Activities of Paeonol and Its Metabolites Through Blocking MAPK/ERK/p38 Signaling Pathway

Abstract: The possible protective and curative effects of paeonol on carrageenan-induced acute hind paw edema in rats and dextran sulfate sodium (DSS)-induced colitis in mice have been evaluated. After oral administration, paeonol (20 and 40 mg/kg) reduced the edema increase in paw volumes and also the development of DSS-induced murine colitis. Furthermore, anti-inflammatory and anti-oxidant activities of paeonol (1) together with its 10 metabolites (M2~M11) were investigated by using in vitro anti-inflammatory and anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 24 publications
(27 reference statements)
5
60
0
Order By: Relevance
“…Another report also showed that Ang 1-7 treated HEK 293T cells at high concentrations redistributed the MAS-1 R to intracellular vesicles and co-localized Ang 1-7 with Rab5 and the adaptor protein complex 2, suggesting regulation by a clathrin-mediated pathway [43]. Enhanced activity of members of the MAPK family, p38 MAPK and ERK1/2 as well as Akt (the downstream target of PI3K), which we observed in colonic sections post DSS treatment (Figs 8-10) has previously been reported in colonic biopsies from IBD patients [44][45][46][47]. Treatment with inhibitors of these signaling molecules ameliorated colitis severity in mice and reduced the disease activity index in patients, underlining their role in IBD pathogenesis [44][45][46][47].…”
Section: Discussionsupporting
confidence: 73%
“…Another report also showed that Ang 1-7 treated HEK 293T cells at high concentrations redistributed the MAS-1 R to intracellular vesicles and co-localized Ang 1-7 with Rab5 and the adaptor protein complex 2, suggesting regulation by a clathrin-mediated pathway [43]. Enhanced activity of members of the MAPK family, p38 MAPK and ERK1/2 as well as Akt (the downstream target of PI3K), which we observed in colonic sections post DSS treatment (Figs 8-10) has previously been reported in colonic biopsies from IBD patients [44][45][46][47]. Treatment with inhibitors of these signaling molecules ameliorated colitis severity in mice and reduced the disease activity index in patients, underlining their role in IBD pathogenesis [44][45][46][47].…”
Section: Discussionsupporting
confidence: 73%
“…Recent research progress on the inhibitory activity of paeonol on the inflammatory reaction is significant (38,39). The mechanism by which paeonol decreases MyD88 and TLR proteins, either by inducing degradation of these proteins or blocking their synthesis, remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Paeonol has a wide range of biological effects, including anti-inflammatory, immune regulatory, anti-tumor, and anti-oxidative effects [15, 16]. Paeonol is used in food additive and traditional oriental medicines in treating various diseases including Alzheimer's diseases [17, 18] and atherosclerosis [19].…”
Section: Introductionmentioning
confidence: 99%